Respostas
respondido por:
1
Boa tarde
PG
u1 = 1
u2 = 3
q = u2/u1 = 3
termo geral
un = u1*q^(n - 1)
729 = 1*3^(n - 1)
3^6 = 3^(n - 1)
n = 7 termos
soma
Sn = u1*(q^n - 1)/(q - 1)
Sn = 1"(3^7 - 1)/(3 - 1)
Sn = 1093
PG
u1 = 1
u2 = 3
q = u2/u1 = 3
termo geral
un = u1*q^(n - 1)
729 = 1*3^(n - 1)
3^6 = 3^(n - 1)
n = 7 termos
soma
Sn = u1*(q^n - 1)/(q - 1)
Sn = 1"(3^7 - 1)/(3 - 1)
Sn = 1093
albertrieben:
se gostou da minha resposta, escolha como a melhor
respondido por:
1
An = 729
a₁ = 1
q = a₂ / a₁
q = 3/1
q = 3
n = ?
An = a₁ * qⁿ⁻¹
729 = 1 * 3ⁿ⁻¹
3ⁿ⁻¹ = 729 / 1
3ⁿ⁻¹ = 729
3ⁿ⁻¹ = 3⁶
n - 1 = 6
n = 1 + 6
n = 7
Sn = a₁ * (qⁿ - 1) / q - 1
S₇ = 1 * (3⁷ - 1) / 3 - 1
S₇ = 2187 - 1 / 2
S₇ = 2186 / 2
S₇ = 1 093
Perguntas similares
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás